Single-camera high-speed stereo-digital image correlation for full-field vibration measurement. (15th September 2017) - Yu, Liping; Pan, Bing
Highlights: A single-camera high-speed stereo-DIC is proposed for full-field 3D vibration measurement. Typical dynamic parameters of a rectangular cantilever aluminum panel are determined from the full-field displacements. The accuracy of the dynamic parameters is verified by FEA and/or accelerometers. The SCHS stereo-DIC is promising for vibration measurements and dynamic parameters identification. Abstract: A low-cost, easy-to-implement single-camera high-speed stereo-digital image correlation (SCHS stereo-DIC) method using a four-mirror adapter is proposed for full-field 3D vibration measurement. With the aid of the four-mirror adapter, surface images of calibration target and test objects can be separately imaged onto two halves of the camera sensor through two different optical paths. These images can be further processed to retrieve the vibration responses on the specimen surface. To validate the effectiveness and accuracy of the proposed approach, dynamic parameters including natural frequencies, damping ratios and mode shapes of a rectangular cantilever plate were extracted from the directly measured vibration responses using the established system. The results reveal that the SCHS stereo-DIC is a simple, practical and effective technique for vibration measurements and dynamic parameters identification.